DISIPLIN KERJA MEMPENGARUHI KINERJA - Ellisyah Mindari (Jurnal Manajemen Kompeten, 2022)
The organization’s goals will be difficult to achieve without work discipline. Studies of the influence of work discipline (preventive discipline, corrective discipline and progressive discipline) on performance together or partially were carried out in this research. This quantitative research survey method, the formulation of the problem is associative in the form of a causa/causal relationship. The population and sample were 50 respondents with census sampling techniques. Data tested for validity, reliability, multiple regression analysis, coefficient of determination, F test and t test used of IBM SPSS Statistic 24. Multiple regression equation is Y=32,266+0,419x1-0,507x2-0,111x3. The coefficient determinant 0,455 means that y is described by x1, x2 and x3 by 45,5%, the remaining 54,5% is explained by other factors. Obtained Fcount 12,816 > Ftable 2,807 meaning x1, x2 and x3 together affect y with a significant degree of 0,000 < α (0,05), so there is a significant effect. The results of the analysis explain that there is a significant effect of preventive discipline and corrective discipline on performance. However, a partial progressive discipline has no significant effect on performance. Preventive discipline has the most dominant effect on performance